Lithium Dendrites: Inside or Outside: Origin of Lithium Dendrite Formation of All Solid‐State Electrolytes (Adv. Energy Mater. 40/2019). Issue 40 (24th October 2019) - Mo, Fangjie; Ruan, Jiafeng; Sun, Shuxian; Lian, Zixuan; Yang, Sangpu; Yue, Xinyang; Song, Yun; Zhou, Yong‐Ning; Fang, Fang; Sun, Guangai; Peng, Shuming; Sun, Dalin
Abstract : The critical step for development of all‐solid‐state lithium metal batteries lies in revealing the origin of lithium dendrite formation in the electrolyte. In article number 1902123, Yun Song, Dalin Sun and co‐workers use the representative electrolyte, LiBH4 to demonstrate that lithium dendrites directly form inside the bulk solid‐state electrolyte, which is like the process in which plants break through a soil bed and rise into the air.